Microcystic stromal tumor resected by laparoscopic surgery - Midori Murakami; Junko Wroblewski; Hidehiro Kawagoe (Wolters Kluwer Medknow Publications, 2017)
We report a case of microcystic stromal tumor (MCST) resected by laparoscopy. MCST is a very rare ovarian tumor with distinctive microcystic features and a characteristic stromal tumor immunophenotype. The present case was a 26-year-old woman who underwent laparoscopic surgery for suspected endometrial cyst of the left ovary. The mass was 8 cm in size and contained bloody fluid, and after attempting cystectomy, we eventually performed left salpingo-oophorectomy with a final postoperative pathological diagnosis of MCST. Although MCST has not yet been associated with malignancy, there are reported links to mutations in the β-catenin gene, and long-term prognosis is still unknown. As MCST resection by laparoscopy has not yet been fully described in the literature, the current case provides an example of when an unexpected, potentially malignant mass is encountered during routine cystectomy and details its subsequent management laparoscopically.